Experimental Evidence for the Effects of Organizational Culture on Managers’ IT Capital Expenditure Decisions (Journal of Applied Business and Economics, 2021)
The research question addressed in this study is whether, in the context of an information technology investment decision, a manager will decide differently in a situation where there is no information about a firm’s organizational culture compared with a situation where the firm’s organizational culture is known to be either bureaucratic or innovative. This paper’s experimental results show that a person will decide differently in response to knowledge of the firm’s organizational culture. Results also show that for the same types of organizational culture there are no significant differences in investment decisions among participants classified as being provincial, transnational, or foreign. Additional analysis shows that personal risk profile is a significant covariate for the group of participants classified as provincials but has no effect on decision-making for participants classified as foreigners and transnationals.
Keywords: business; economics; organizational culture; bureaucratic; innovative; personal risk profile; provincial